5-HT7 receptor signaling: improved therapeutic strategy in gut disorders - Kim, Janice J.; Khan, Waliul I. (Frontiers in Behavioral Neuroscience, 2014)
Serotonin (5-hydroxytrytamine; 5-HT) is most commonly known for its role as a neurotransmitter in the central nervous system. However, the majority of the body’s 5-HT is produced in the gut by enterochromaffin (EC) cells. Alterations in 5-HT signaling have been associated with various gut disorders including inflammatory bowel disease (IBD), irritable bowel syndrome (IBS) and enteric infections. Recently, our studies have identified a key role for 5-HT in the pathogenesis of experimental colitis. 5-HT7 receptors are expressed in the gut and very recently, we have shown evidence of 5-HT7 receptor expression on intestinal immune cells and demonstrated a key role for 5-HT7 receptors in generation of experimental colitis. This review summarizes the key findings of these studies and provides a comprehensive overview of our current knowledge of the 5-HT7 receptor in terms of its pathophysiological relevance and therapeutic potential in intestinal inflammatory conditions, such as IBD.